Antimicrobial capacity of the freshwater planarians against S. aureus is under the control of Timeless. Issue 7 (3rd October 2017) - Tsoumtsa, Landry Laure; Torre, Cedric; Trouplin, Virginie; Coiffard, Benjamin; Gimenez, Gregory; Mege, Jean-Louis; Ghigo, Eric
ABSTRACT: Planarians, which are non-parasitic flatworms, are highly resistant to bacterial infections. To better understand the mechanisms underlying this resistance, we investigated the role of the circadian machinery in the anti-bacterial response of the freshwater planarian Schmidtea mediterranea . We identified Smed-Tim from S. mediterranea as a homolog of the mammalian clock gene Tim . We showed via RNA interference that Smed-Tim is required for the anti-microbial activities of Schmidtea mediterranea against Staphylococcus aureus infection during the light/dark cycle. Indeed, S. aureus infection leads to the expression of Smed-Tim, which in turn promotes Smed-Traf6 and Smed-morn2, but not Smed-p38 MAPK expression, 2 master regulators of planarian anti-microbial responses.